2018
DOI: 10.1177/2324709618789194
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Slow-Flow Phenomenon as an Underrecognized and Treatable Source of Chest Pain: Case Series and Literature Review

Abstract: Background. Coronary slow-flow phenomenon (CSFP) is characterized by delayed distal vessel opacification of contrast, in the absence of significant epicardial coronary stenosis. CSFP has been reported as a cause of chest pain and abnormal noninvasive ischemic tests and is often underrecognized. Material and Methods. Charts and angiographic records from our institution were reviewed to identify 15 consecutive patients who were diagnosed with CSFP from January 2016 to January 2017. Results. Of the 15 patients (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 24 publications
3
26
1
Order By: Relevance
“…It is likely based on these findings that CSFP is multifactorial, altering the endothelium on a biochemistry level. Coronary angiograms in these patients with CSFP are classically referred to as "negative and normal," or to have "minimal non-obstructive disease," which leads to patients being referred to as negative cardiac catheterization myocardial infarctions [19,20]. These findings correlate with what was seen objectively within our case report.…”
Section: Discussionsupporting
confidence: 82%
“…It is likely based on these findings that CSFP is multifactorial, altering the endothelium on a biochemistry level. Coronary angiograms in these patients with CSFP are classically referred to as "negative and normal," or to have "minimal non-obstructive disease," which leads to patients being referred to as negative cardiac catheterization myocardial infarctions [19,20]. These findings correlate with what was seen objectively within our case report.…”
Section: Discussionsupporting
confidence: 82%
“…Aldosterone is one of the other proteins that regulate the rigidity of vascular tone by increasing accumulation of fibrotic tissue and is responsible in endothelial dysfunction. The result of this study was different with the previous studies [1], [13], [14]. The study showed II genotype was the risk factor in CSFP patients.…”
Section: Discussioncontrasting
confidence: 99%
“…TIMI frame counts were evaluated in 15 frames per second, which was multiplied by two times for 30 frame equivalence 22 . The corrected TIMI frame count for LAD was calculated by dividing the corrected TIMI frame count of a left descending artery by 1.7.…”
Section: Methodsmentioning
confidence: 99%